2022
DOI: 10.3390/rs14030798
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Quality Indicators for Differential Interferometric Synthetic Aperture Radar Data

Abstract: Satellite-based interferometric synthetic aperture radar (InSAR) is an invaluable technique in the detection and monitoring of changes on the surface of the earth. Its high spatial coverage, weather friendly and remote nature are among the advantages of the tool. The multi-temporal differential InSAR (DInSAR) methods in particular estimate the spatio-temporal evolution of deformation by incorporating information from multiple SAR images. Moreover, opportunities from the DInSAR techniques are accompanied by cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Future developments of this work will aim at assessing the performance of the adopted method in terms of the existing ones [17,19]. Quality indicators for the obtained products, e.g., [44], can be employed to provide further validation and to optimally tune the main algorithm parameters, i.e., minimum average coherence, minimum image redundancy, and the threshold for the equivalent spatial coherence used for the point selection. The study of the displacement time series has revealed the presence of abrupt changes due to the seismic activity that are extremely dangerous for the built environment and infrastructures.…”
Section: Discussionmentioning
confidence: 99%
“…Future developments of this work will aim at assessing the performance of the adopted method in terms of the existing ones [17,19]. Quality indicators for the obtained products, e.g., [44], can be employed to provide further validation and to optimally tune the main algorithm parameters, i.e., minimum average coherence, minimum image redundancy, and the threshold for the equivalent spatial coherence used for the point selection. The study of the displacement time series has revealed the presence of abrupt changes due to the seismic activity that are extremely dangerous for the built environment and infrastructures.…”
Section: Discussionmentioning
confidence: 99%
“…The results were validated against in-situ GNSS measurements. Future developments will include implementing an interferogram filtering stage (Pepe et al, 2015) before the interferogam selection stage, as well as analysing the quality of the produced results using proper indicators (Wassie et al, 2022) and implementing time series classifiers (Mirmazloumi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…𝛼 0 , 𝛽 0 and 𝛽 1 stands for thresholds to be determined by operators. Detailed formulation of procedures for the quality score assignment is presented inWassie et al (2022).…”
mentioning
confidence: 99%